Attributes of Anopheles gambiae swarms in South Central Uganda - Birungi, Krystal; Mabuka, Danspaid P; Balyesima, Victor; Tripet, Frederic; Kayondo, Jonathan K; Kayondo, Jonathan K (BioMed Central Ltd, 2024)
Abstract Anopheles gambiae continues to be widespread and an important malaria vector species complex in Uganda. New approaches to malaria vector control are being explored including population suppression through swarm reductions and genetic modification involving gene drives. Designing and evaluating these new interventions require good understanding of the biology of the target vectors. Anopheles mosquito swarms have historically been hard to locate in Uganda and therefore have remained poorly characterized. In this study we sought to identify and characterize An. gambiae s.l mosquito swarms in three study sites of high An. gambiae s.l prevalence within Central Uganda. Nine sampling visits were made to three villages over a 2-year period. Sampling targeted both wet and dry seasons and was done for 2 days per village during each trip, using sweep nets. All swarm data were analysed using the JMP 14 software (SAS Institute, Inc., Cary, NC, USA), parametrically or non-parametrically as appropriate. Most of the An. gambiae s.s. swarms sampled during this study were single-species swarms. However, some mixed An. gambiae s.s. and Culex spp. mosquito swarms were also observed. Swarms were larger in the wet season than in the dry season. Mean swarm height ranged from 2.16 m to 3.13 m off the ground and only varied between villages but not by season. Anopheles gambiae mosquitoes were present in all three villages, preferred to swarm over bare ground markers, and could be effectively sampled by field samplers. This study demonstrated that An. gambiae s.l swarms could be effectively located and sampled in South Central Uganda and provided in-depth descriptions of hitherto poorly understood aspects of An. gambiae local swarm characteristics. Swarms were found close to inhabited households and were greater in size and number during the rainy season. Anopheles gambiae s.s swarms were significantly associated with bare ground markers and were sometimes at heights over 4 m above the ground, showing a necessity to develop tools suitable for swarm sampling at these heights. While mixed species swarms have been reported before elsewhere, this is the first documented instance of mixed genus swarms found in Uganda and should be studied further as it could have implications for swarm sampling explorations where multiple species of mosquitoes exist.
Keywords: Swarm, Mixed swarms, Mating behaviour, Anopheles gambiae, Vector ecology, Sampling, Malaria